THE EFFECT OF OXYTOCIN MASSAGE ON THE IMPROVEMENT OF BREAST MILK PRODUCTION IN POSTPARTUM MOTHERS AT SURYANI CLINIC, MEDAN JOHOR, KWALA BEKALA, MEDAN CITY - Anita Yasmin; Fatlipi; Nurhaidakaban (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: The 2023 Indonesian Health Survey (SKI) recorded exclusive breastfeeding coverage of 68.6% among infants aged 0–5 months, but only 55.5% of infants were still exclusively breastfed at six months well short of the 80% national target. Globally, WHO and UNICEF reported an exclusive breastfeeding rate of 48% in 2023. A recurring barrier is insufficient milk output during the first days after delivery, which stems from inadequate stimulation of oxytocin and prolactin, the two hormones that govern milk synthesis and ejection. Oxytocin massage is a non-pharmacological measure intended to trigger this hormonal response. Objective: To determine the effect of oxytocin massage on the smoothness of breast milk production in postpartum mothers at Suryani Clinic, Medan Johor, Kwala Bekala, Medan City, in 2024. Methods: A quasi-experimental study with a two-group pre-test and post-test design was conducted on 44 postpartum mothers selected by purposive sampling and allocated into an intervention group (n = 22) and a control group (n = 22). Milk production was measured with a 16-item observation sheet before the intervention and again after three consecutive days of oxytocin massage. Univariate analysis described respondent characteristics; the independent samples t-test compared the change in observation scores between groups. Results: Most respondents were 19–25 years old (22; 50.0%), primiparous (25; 56.8%), senior high school graduates (32; 72.7%), and not employed (23; 52.3%). Before the intervention, 36 respondents (81.8%) had unsatisfactory milk production. Following oxytocin massage, 30 respondents (68.2%) achieved smooth milk production. Within the intervention group the proportion with smooth production rose from 3 mothers (13.6%) to 21 mothers (95.5%), whereas the control group moved from 5 mothers (22.7%) to 9 mothers (40.9%). The independent samples t-test yielded p = 0.000 (p < α = 0.05). Conclusion: Oxytocin massage significantly improves the smoothness of breast milk production in postpartum mothers. Midwives are encouraged to incorporate the technique into routine postnatal care and to teach it to husbands and family members as lactation support.